2022
DOI: 10.3389/fpls.2022.884476
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide identification of lncRNAs and circRNAs having regulatory role in fruit shelf life in health crop cucumber (Cucumis sativus L.)

Abstract: Cucumber is an extremely perishable vegetable; however, under room conditions, the fruits become unfit for consumption 2–3 days after harvesting. One natural variant, DC-48 with an extended shelf-life was identified, fruits of which can be stored up to 10–15 days under room temperature. The genes involved in this economically important trait are regulated by non-coding RNAs. The study aims to identify the long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) by taking two contrasting genotypes, DC-48 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The potential candidate genes associated with extended shelf-life are the genes encoding cell-wall degradation enzymes, biosynthesis of ethylene and key upstream transcription factors. Cell walls, tissue turgors, and cuticles are reported to be critical players in cell wall stability and the retention of fruit rmness (Dey et al, 2022). The retention of green colour in the genotype, DC-48 was mainly due to the slower degradation of chlorophyll after harvest.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The potential candidate genes associated with extended shelf-life are the genes encoding cell-wall degradation enzymes, biosynthesis of ethylene and key upstream transcription factors. Cell walls, tissue turgors, and cuticles are reported to be critical players in cell wall stability and the retention of fruit rmness (Dey et al, 2022). The retention of green colour in the genotype, DC-48 was mainly due to the slower degradation of chlorophyll after harvest.…”
Section: Introductionmentioning
confidence: 98%
“…Cucumber fruits are often consumed in their unripe green form, as the ripe yellow form is bitter and acidic. However, the storage of fresh cucumber fruits is a complex process that requires cost-intensive storage facilities to keep them marketable for an extended period (Friedman 2020; Dey et al 2022). Moreover, cucumber fruits are not well-suited for storage at low temperatures due to chilling damage, which rules out the use of cooling, a common method to prolong the shelf life of fresh items (Paul et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the potential importance of lncRNAs as modulators of the development (22, 23) or the response to biotic (2426) or abiotic (27, 28) stress conditions in diverse Cucurbitaceae family members. However, detailed information about lncRNAs in cucurbits is limited, and only a list of unclassified and barely characterized lncRNAs in cucumber, melon and watermelon are currently available in GreeNC (29), PLncDB V2.0 (30) or CANTATAdb 2.0 (31), the most relevant databases containing plant lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…HOTAIR (Hox Antisense Intergenic RNA) is a trans-acting lncRNA in humans that transports itself to other locations on different chromosomes and regulates the gene expression ( Chen and Carmichael, 2010 ; Song et al., 2016 ). Apart from the extensive studies done in humans and other mammals, various plant lncRNAs have also been identified including Arabidopsis thaliana ( Lu et al., 2017 ), wheat ( Lu et al., 2020 ), rice ( Wang et al., 2018 ; Zhou et al, 2021 ), maize ( Li et al., 2014 ), tomato ( Yang et al., 2019 ), cucumber ( He et al., 2020 ; Dey et al., 2022 ), pearl millet ( Kumar et al., 2022 ), and watermelon ( Sun et al., 2020 ). LDMAR (Long Day Specific Male-sterility-associated RNA) which is a 1236 bp long lncRNA can regulate the male sterility sensitive to photoperiod in rice.…”
Section: Introductionmentioning
confidence: 99%